Patents as Collateral - Jean-Bernard Chatelain; Kirsten Ralf; Bruno Amable (Journal of Economic Dynamics & Control, 2010)
This paper studies how the assignment of patents as collateral determines the savings of firms and magnifies the effect of innovative rents on investment in research and development (R&D). We analyse the behaviour of innovative firms that face random and lumpy investment opportunities in R&D. High growth rates of innovations, possibly higher than the real rate of interest, may be achieved despite financial constraints. There is an optimal level of publicly funded policy by the patent and trademark office that minimizes the legal uncertainty surrounding patents as collateral and maximizes the growth rate of innovations.
Keywords: D9; G2; G3; O1; O3; O4; 330; Patents; Collateral; Growth; Innovation; Research and Development; Credit rationing; Patent; Collateral (Security); Growth theory; Innovation; Research; Credit rationing